Report to the President and Congress Ensuring Leadership in Federally Funded Research and Development in Information Technology - Horvitz, Eric (2015)
About the President’s Council of Advisors on Science and Technology The President’s Council of Advisors on Science and Technology (PCAST) is an advisory group of the Nation’s leading scientists and engineers, appointed by the President to augment the science and technology advice available to him from inside the White House and from cabinet departments and other Federal agencies. PCAST is consulted about, and often makes policy recommendations concerning, the full range of issues where understandings from the domains of science, technology, and innovation bear potentially on the policy choices before the President. For more information about PCAST, see www.whitehouse.gov/ostp/pcast
Executive Office of the President President's Council of Advisors on Science and Technology